A Secure Data Transmission By Integrating Cryptography And Video Steganography - P K, Shafna (IJRDO -Journal of Computer Science Engineering, 2015)
Advances in digital content transmission have increased in past few years. Security and privacy issues of the transmitted data have become an important concern in multimedia technology. In this paper proposes a video steganography method for transmitting data securely. Steganography means covered writing it includes process of concealing information within other file and also conceals the fact that a secret message is being sent .Video Steganography is to hide the existence of the message from unauthorized party using Video as cover file and hiding data in video. In this work a very simple and real time algorithm is used for the encryption of the images which are the basic building blocks of any video file. In the proposed research paper the video is distributed into the photo frames using a matlab code and all the frames are sequentially stored. Each such frame contains a combination of red, blue and green layers. If we consider a pixel as an 8 bit value than each pixel has the value in the range of 0 to 255. In this work, for each frame four pixels situated at the top left and right and the bottom left and right corner are modified so as to insert text in each image. Text data is encrypted using AES algorithm. After the completion of the pixel value changing all the images is placed in a sequential manner and then all the frames are cascaded for generation of the original video file with encryption. This new video is almost similar to the original video file with no changes visible to the naked eye.